Pengaruh Promosi, Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Sepeda Motor Yamaha Jupiter All Variant Pada Yamaha Mataram Sakti Cabang Soegiyopranoto Semarang - Pryas Aji Pramana; Wahyu Hidayat; Handoyo Djoko Waloejo (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect of the promotion, service quality and price on purchase decisions  of Yamaha Jupiter All variant at  Mataram Sakti  , Soegiyopranoto Branch Semarang. This study used  explanatory research. Primary data obtained from respondents using data collection instruments such as questionnaires and secondary data gained from the site in the form of a percentage of sales of Yamaha motorcycles with other motorcycle brands. The population of this research is  consumers who purchase  Yamaha Jupiter All Variant in Yamaha Mataram Sakti Soegiyopranoto  branch, Semarang at the years of 2009-2011 with a sample of 92 respondents from 1179 population were using purposive sampling technique. Analysis of the data used in this study is the validity and reliability, Cross Tabulation Analysis (Crosstab), Coefficient of Correlation, Simple Linear Regression, Multiple Linear Regression, Coefficient of Determination, t-test and F Test. Y = 0.018 + 0.002 X1 + 0.263 X2 + 0.172 X3. The analysis showed variable of promotion, service quality, price, has a positive and significant impact on the purchase decision variables. Hypothesis that tested using t-test showed that the three independent variables studied proved to significantly affect the dependent variable purchase decision. Through the T test can be seen that the variable promotion, service quality and price significantly effect together in a purchase decision. degree of closeness of the relationship between the variables promotion, service quality, and price of the purchase decision variable is promotion 0,408 , service quality 0,731 , Price 0,508 .Through the F test can be seen that the variable promotion, service quality and price significantly effect together in a purchase decision. degree of closeness of the relationship between the variables promotion, service quality, and price of the purchase decision variable is equal to 0.745, so it can be concluded that the strength of association (correlation) between variables linear promotion, service quality, and price of the purchase decision variables is strong. The company should give some promotion variations and increase the performance of the service officer in the quickness ability of giving service and decrease the number of fault that did by the company.